Twelve years of soil preservation and rehabilitation on the Rio do Peixe watershed: promoting conservation agriculture. (22nd July 2021) - Vischi Filho, Oswaldo Julio; Yoshikatsu Kanno, Oscar; Mikio Arabori, Roberto; Bernardoni Caldas, João Flávio; Barros Penteado, Raul; Menegucci Scachetti, Edna Aparecida; Aparecido Quiessi, Jorge; Braghetta Camargo, Marcelo; Carvalho, Tiago
Abstract: This study aimed to evaluate the works undertaken on the Rio do Peixe watershed by the Coordination of Agricultural Defense (CDA) over 12 years, where conservationist agriculture practices have been used since 2007 to promote the recovery of degraded areas, the reduction of erosion and the improvement of water quality. In addition, we evaluated the performance of innovative diagnostic strategies used to identify erosion spots in the river basin. The effective supervision of large farmland areas is a common problem that requires the development of cost‐effective tools while keeping a close interaction with stakeholders. From 2007 to 2017, 176 properties (23, 103 ha) were inspected and notified to fulfill the soil conservation laws, using the Conventional CDA methodology (i.e., field assessment by an agronomist). In the Marília sector, the Innovative CDA Methodology (with remote sensing) was used, enabling the audit of 52 properties covering 27, 775 ha in 2 years. Each landowner was requested to submit technical projects using conservationist practices to be implemented under CDA guidelines. Methods included vegetation cover and crop rotation (control of laminar erosion) and implementation of agricultural terraces, bypass channels, and containment basins (management of gullies erosion). The activities carried out promoted a shift from conventional agriculture, which was impacting soil fertility and water quality, towards conservation agriculture. Degraded pastures were converted into annual cropping areas using No‐Tillage (zero tillage) farming techniques. Other pastures were recovered, through Integrated Crop‐Livestock Systems, increasing its stocking rate. The undertaken activities were labor‐intensive but beneficial for farmers and for the quality of waterbodies.